Analisa Perbandingan Metode Saw, Wp Dan Topsis Dalam Menentukan Kandidat Perwakilan Lomba Kompetensi Siswa Sekolah Menengah Kejuruan - Trisna Ayu Silvia; Aldiansyah; Muhamad Husni Ramadhan; Ovi Nur Afifa; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The student competition competition is an annual competition between students at the vocational level depending on the productive skill subjects taught by students at vocational schools, the participants in this LKS competition are in accordance with the OSN (National Science Olympiad) which is held at the junior high/high school level. This Student Competency Competition is important to do because in order to be able to measure the success of the educational process in schools. The decision support system methods used include SAW (Simple Addictive Weighting), WP (Weighted Product) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). These methods are used in order to get accurate results. Calculations using the SAW, WP and TOPSIS methods get different results for the lowest alternative. When using the SAW and WP alternative methods, the highest obtained was Ovi Nur Afifa and the lowest was Aldiansyah. Meanwhile, for the TOPSIS method the lowest is Trisna Ayu Silvia and the highest remains the same. The SAW (Simple Addictive Weighting), WP (Weighted Product) and TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) methods are very appropriate methods for determining candidates in selecting something. Because the calculation results from these methods are very accurate.